The Erotics of Salvage - Yargo, John (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2023)
In the aftermath of the storm in The Tempest, as Miranda suffers vicariously with the shipwrecked passengers, Prospero imposes meaning onto the environmental catastrophe. Imbricating maritime salvage, physical saving, and theological salvation, Prospero insists on a temporality of supersession in which catastrophe allows one political order to displace an older, corrupt paradigm. But the act of salvaging deepens Miranda’s erotic attachment to Ferdinand and complicates the social affiliations of the island. Alternately, Caliban, inverting the erotics of salvage, dramatizes how racialized perception saturates experiential encounters with the storm.